DEVELOPMENT OF DIAMONOLOGICAL COMPETENCE OF FUTURE PRIMARY SCHOOL TEACHERS IN THE PROCESS OF PROFESSIONAL TRAINING - Lapshyna, Iryna; Lyubchak, Lyudmila; Franchuk, Nataliia; Vasylyuk, Alla; Komarivska, Nadiia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The implementation of active forms and methods of group interaction in the educational process is recognized as a perspective means of developing future teachers’ communication. From the authors’ standpoint, it is necessary to re-evaluate the developmental potential of such specific methods as discussion methods (group discussion, analysis and commentary of situations); play methods (role-, director-, and counterplays) and play psychotherapy, trainings of interpersonal sensitivity, personal growth, techniques of non-verbal interaction and others. The topicality of such re-evaluation is caused not only by the reform processes in the education system of Ukraine, but also by the modern challenge to the whole system of world education - the need for large-scale implementation of distance forms of the educational process organization in connection with the pandemic situation. The survey of future primary school teachers conducted by the authors, indicates a low readiness of modern teachers to use active teaching methods for training schoolchildren of different age groups, to organize speech interaction with students based on emotional involvement in work, critical re-evaluating of self-position, frank and reasoned expression of thoughts and feelings. In this regard, the issues of the development of diamonological competence of the higher education institutions students acquire additional relevance in the pedagogical discussion.